2018
DOI: 10.1136/openhrt-2018-000812
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic power of cardiopulmonary exercise testing in Fontan patients: a systematic review

Abstract: ObjectiveExercise impairment is common in Fontan patients. Our aim is to systematically review previous literature to determine the prognostic value of exercise capacity in older adolescent and adult Fontan patients with respect to late outcome. Additionally, we reviewed the determinants of exercise capacity in Fontan patients and changes in exercise capacity over time.MethodsPubMed, CINAHL, Embase, The Cochrane Library and Scopus were searched systematically for studies reporting exercise capacity and late ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 45 publications
3
48
0
Order By: Relevance
“…Of the patients in the FO group, 98% had an increased VE/VCO2. These results concur with the previous studies and show that exercise limitation is common in this special group of patients [2,15,16]. The reasons for the reduced exercise performance in patients after FO seem to be associated with a combination of different mechanisms.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Of the patients in the FO group, 98% had an increased VE/VCO2. These results concur with the previous studies and show that exercise limitation is common in this special group of patients [2,15,16]. The reasons for the reduced exercise performance in patients after FO seem to be associated with a combination of different mechanisms.…”
Section: Discussionsupporting
confidence: 92%
“…CPET is a widely acknowledged tool as it provides information about not only exercise capacity but also prognosis, including the need for heart transplantation [15]. The results of the present study corroborate with a well-known observation that patients with Fontan physiology have reduced exercise capacity.…”
Section: Discussionsupporting
confidence: 90%
“…The physiological mechanisms of this limitation includes inadequate preload augmentation to the single ventricle (14), inadequate heart rate reserve (15), and poor conditioning with relative skeletal muscle weakness (16). Poor exercise performance is associated with acute cardiovascular decompensation, need for heart transplantation, and early mortality (17). There is evidence however that a few Fontan patients achieve normal exercise performance (6).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have found that the peak oxygen consumption is one of the best predictors of morbidity or mortality in a variety of cardiovascular conditions including congestive heart failure, 19,20 pulmonary hypertension, 21 tetralogy of Fallot, 22 transposition of the great arteries, 23 and Fontan circulations. 3 The study by Inuzuka et al 1 found that peak oxygen consumption and heart rate reserve data can be used to generate estimates for 5-year survival in many adults with CHD. However, in their study a majority of patients had low peak respiratory exchange ratio values <1.1, suggesting that a large fraction of the patients did not expend adequate effort and terminated exercise before reaching their cardiovascular limit.…”
Section: Discussionmentioning
confidence: 99%